PERANCANGAN SISTEM MONITORING DAN EVALUASI PROGRAM KOMUNIKASI PUBLIK DI DINAS KOMINFO KOTA MEDAN - Ramadhan, Agung Wahyu; Ikhwan, Ali (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
Information technology plays an important role in improving transparency, efficiency and effectiveness of public services, including in the government sector. The Communication and Informatics Office (Diskominfo) of Medan City has a strategic role in managing public information and technology-based communication services. One of its important tasks is monitoring and evaluating public communication programs to ensure the effectiveness of information dissemination. However, the main challenge faced is the lack of an integrated system in managing and analyzing the effectiveness of communication programs. Inefficiencies in data management and the lack of systematic monitoring can hinder the optimization of public communication. Therefore, the development of a Monitoring and Evaluation System for Public Communication Programs is a solution to improve the efficiency of data management, accelerate analysis, and strengthen coordination between related units. By implementing a more structured and technology-based system, Diskominfo Medan can optimize information dissemination strategies and increase community involvement. This step is in line with the broader strategy in facing digital challenges, strengthening the role of technology, and improving the competitiveness and effectiveness of government in the global era.